WOMEN'S HIGHER EDUCATION: A DILEMMA OF CHOICES - David-Kredl, Priscilla (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1989)
This article deals with a number of factors which pressure contemporary women into selecting academic programs traditionally dominated by males. Motivated by the goals of higher financial rewards, status, and power, women who prepare themselves for nontraditional occupations and lifestyles were found in this research to be more likely than women in traditional occupations to remain unmarried and for childless. The findings also show that women who select the more traditional academic programs tend to accept the traditional roles and lifestyles supported by societal norms. RÉSUMÉ Cet article traite d'un certain nombre de facteurs qui poussent les femmes d'aujourd'hui à choisir des programmes d'études traditionellement réservés aux hommes. Motivées par l'appât de gains financiers et d'un statut social plus élevés et de pouvoirs accrus, les femmes qui se préparent à des professions et des modes de vie non traditionels ont plus de chances de rester célibataires et (ou) sans enfant. L'auteur de cette étude conclut que les femmes qui optent pour des programmes universitaires classiques acceptent plus facilement les rôles et les modes de vie traditionnels reconnus par la société.